Kuntowijoyo's Islamic Epistemology and Its Implications in Islamic Thought - Wijaya, Roma; Hidayat, M. Riyan (Pascasarjana UIN ANTASARI Banjarmasin, 2024)
This article outlines an epistemological formulation of Islamic scholarship from a Muslim historian, literati, sociologist, and scholar named Kuntowijoyo. Islam seems incapable of matching science. This is coupled with subjective ideologies still raised by Islamic figures or organizations. Kunto provides a paradigm to explain the phenomena that occur (factually) and achieve the transformative ideals of Islam. This research is library research (literature review) with data collection using documentation. Metode descriptive-analytical analysis that outlines the basic meaning of Islamic science and ilmu social profetik then sees its implications for the caliphate of Islamic thought. The result of this article is that the Islamic Science thrown by Kuntowijoyo seeks that Islam is not seen as ideological because it will cause subjectivity among its adherents. Islam is formed in scientific theory that all human beings, especially Muslims, can recognize. This problem departs from Kunto's anxiety about the phenomenon of Indonesian society upholding myths and ideologies but forgetting the awareness of science. The implications for Islamic thought must be an effort to formulate Islam systematically in the form of science.